2017
DOI: 10.1088/2057-1976/aa5a31
|View full text |Cite
|
Sign up to set email alerts
|

Differences in respiratory mechanics estimation with respect to manoeuvres and mathematical models

Abstract: The aim of mechanical ventilation (MV) is to provide sufficient breathing support for critically ill patients with respiratory failure in the intensive care unit (ICU). However, the application of inappropriate MV settings can result in ventilator induced lung injury (VILI) and exacerbate respiratory dysfunction. To prevent VILI, respiratory mechanics properties such as elastance and resistance can be estimated at the bedside to guide MV settings. Different models or methods provide different information and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…The realtime and hourly data analysis in CARENet, or similar system, can provide continuous monitoring to optimize decision making at the bedside in a clinically timely fashion. Conversely, the daily summary trend shows longer term evolution of patient condition and response, providing unique insight into patient response to the overall MV treatment approach [86]. Both outcomes provide significant input to further guide and optimize care.…”
Section: Discussionmentioning
confidence: 99%
“…The realtime and hourly data analysis in CARENet, or similar system, can provide continuous monitoring to optimize decision making at the bedside in a clinically timely fashion. Conversely, the daily summary trend shows longer term evolution of patient condition and response, providing unique insight into patient response to the overall MV treatment approach [86]. Both outcomes provide significant input to further guide and optimize care.…”
Section: Discussionmentioning
confidence: 99%
“…CD varies from 0 to 1, CD = 1 represents a perfect fit and CD = 0 represents no fit at all. Although respiratory mechanics is a non-linear process, it is reported that the FOM is capable of correctly predicting respiratory mechanics in ICU patients (Kretschmer et al 2017). In this study, we employ FOM for the prediction of respiratory resistance and compliance of the ex vivo porcine lungs.…”
Section: Model Based Prediction Of Resistance and Compliancementioning
confidence: 99%